2021
DOI: 10.18632/aging.202544
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation perturbations may link altered development and aging in the lung

Abstract: Fetal perturbations in DNA methylation during lung development may reveal insights into the enduring impacts on adult lung health and disease during aging that have not been explored altogether before. We studied the association between genome-wide DNA-methylation and post-conception age in fetal-lung (n=78, 42 exposed to in-utero-smoke (IUS)) tissue and chronological age in adult-lung tissue (n=160, 114 with Chronic Obstructive Pulmonary Disease) using multi-variate linear regression models with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…This clock site is in the promoter region and positively correlates with age, similarly to what we observed in both mouse and NMR (r = 0.463, p = 2.67E-06). In addition, a CpG site in the promoter region of human Mab21l2 (cg05878390 in the 450k array) was among the top 20 significant differentially methylated CpGs associated with age in a fetal lung dataset of in-utero-smoke and control samples at 57-122 days of gestation 50 . This gene was also differentially methylated in the dorsolateral prefrontal cortex of opioid users in humans, and there was a significant association between opioid use and the Levine phenotypic age 51 .…”
Section: Discussionmentioning
confidence: 99%
“…This clock site is in the promoter region and positively correlates with age, similarly to what we observed in both mouse and NMR (r = 0.463, p = 2.67E-06). In addition, a CpG site in the promoter region of human Mab21l2 (cg05878390 in the 450k array) was among the top 20 significant differentially methylated CpGs associated with age in a fetal lung dataset of in-utero-smoke and control samples at 57-122 days of gestation 50 . This gene was also differentially methylated in the dorsolateral prefrontal cortex of opioid users in humans, and there was a significant association between opioid use and the Levine phenotypic age 51 .…”
Section: Discussionmentioning
confidence: 99%
“…We have previously identified DNA methylation of transcription factors in a lung tissue EWAS. 60 , 61 In this study, we identified HDAC1, SPI1, CREBBP, RERE, FBP1, and ZFPM1 as the top genes implicated in transcription factor binding pathways. Of particular interest is the gluconeogenic enzyme FBP1 (Fructose-Bisphosphatase 1) as it was recently shown to aggravate oxidative stress-induced apoptosis in bronchial epithelial cells by suppressing the nuclear factor erythroid-derived 2-related factor 2 (Nrf2) pathway, which is protective in asthmatic patients by maintaining the structure of the bronchial epithelial barrier.…”
Section: Discussionmentioning
confidence: 90%
“…Methylation is an important epigenetic modification mechanism in cancer ( 12 ), occurring at DNA ( 13 ), RNA ( 14 ), and protein ( 15 , 16 ) levels. DNA methylation is involved in the regulation of target gene expression ( 17 ); RNA methylation is involved in the regulation of transcription, messenger RNA (mRNA) splicing, nuclear export, and translation ( 18 ); and protein methylation is involved in the regulation of activity, translation, localization, and signaling of protein ( 19 ).…”
Section: Introductionmentioning
confidence: 99%